Work Responsibilities Stress among Academicians in Private Universities in Malaysia - Zakaria, Sabarudin; ., Arnifa Asmawi (Journal of Education and Vocational Research, 2015)
Increasing numbers of private universities in Malaysia has caused a great competition and expectation that forces the education providers to offer synergy and value-added services to their students. High expectation form students, financial constraint, countless job responsibilities and ‘education as business’ orientation adopted by private universities, are among stressors to its academicians. Thus cause dangerous health complication; hypertension, heart attack, migraine, depression, eating disorder, besides some consider migrating and leaving their job. This study aims to explore the causes and main contributor of stress among these academicians with regards to job responsibilities of teaching, researching and administrative task. The gained result at the end of this study is not entirely purpose to change the whole academician job scope in the industry, but as a guide be it university or the government, in designing or developing new policy for their respective institutions.